Health Promoting Effects of Ziziphus mauritiana : An Overview - Akassh M; Fathima T; Mruthunjaya K (International Journal of Research in Pharmaceutical Sciences, 2020)
Natural products are the main source for an alternative system of medicine. Ziziphus mauritiana, commonly known as jujubes, belongs to the family Rhamnaceae and is majorly found in the Indian subcontinent. They are traditionally used to treat chronic bronchitis, insomnia, diabetes, diarrhoea, abscesses, wounds, liver diseases, fever, sleeplessness, constipation, urinary diseases, and abdominal pains. Over the course of many years, various parts of Ziziphus mauritiana has been found to possess hair growth stimulating, anti-platelet aggregating, anti-inflammation, wound-healing, anti-obesity, antibacterial, and antioxidant effects. Various peer-reviewed research articles were collected from SCOPUS, PubMed, Google, Research Gate, and Web of Science databases. A total of 26 papers were selected based on their relevance. Acetyljujuboside B, Mauritine A, and Jujuboside A are some of the numerous chemical constituents present in Ziziphus mauritiana. The present review is an effort to provide a comprehensive review of the literature on the health-promoting effects of Ziziphus mauritiana.